2012
DOI: 10.1007/s11356-012-0870-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Rhodococcus strain with phenol-degrading ability and its potential use for tannery effluent biotreatment

Abstract: Based on these results, Rhodococcus sp. CS1 could be an appropriate microorganism for bioremediation of tannery effluents or other phenol-containing wastewaters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Since the bioremediation efficiency in 3:1 diluted tannery effluent was less than 1:1 diluted effluent, the latter was preferred for further experiments on tannery effluent biotreatment.An appreciable extent of growth, decolorization, dechlorination, and Cr 6+ removal in diluted as compared to undiluted effluent could be due to reduced toxicity of metals and organic pollutants upon dilution. Contrary to our findings, Paisio et al [7] observed highest growth of Rhodococcus sp. CS1 in pure tannery wastewater as compared to diluted (25, 50 and 75%) effluent.…”
Section: Bioremediation Of Diluted Tannery Effluentcontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the bioremediation efficiency in 3:1 diluted tannery effluent was less than 1:1 diluted effluent, the latter was preferred for further experiments on tannery effluent biotreatment.An appreciable extent of growth, decolorization, dechlorination, and Cr 6+ removal in diluted as compared to undiluted effluent could be due to reduced toxicity of metals and organic pollutants upon dilution. Contrary to our findings, Paisio et al [7] observed highest growth of Rhodococcus sp. CS1 in pure tannery wastewater as compared to diluted (25, 50 and 75%) effluent.…”
Section: Bioremediation Of Diluted Tannery Effluentcontrasting
confidence: 99%
“…Cr 6+ is highly soluble, mutagenic and carcinogenic whereas, Cr 3+ is less soluble and hence less toxic [5]. In addition, it is well known that leather industries generate complex wastewater containing not only chromium but also other toxic compounds like phenol and its derivatives [6,7]. Phenolic compounds also contribute to offflavor problems in drinking and food processing waters.…”
Section: +mentioning
confidence: 99%
“…B9. A similar microbial removal of phenol from tannery wastewater using Rhodococcus strain has been reported by Paisio et al [32] The strain was also active in decontaminating phenol from the wastewater at high phenol concentrations and showed 100% phenol removal but with lower degradation rates. In the presence of higher phenol content of 1.0 and 2.0 mM, strain B9 resulted in complete removal of phenol content at 72 and 96 h, respectively (Figure 4 effluents by pure culture of Acinetobacter sp.…”
Section: Application Of Strain B9 In Dephenolisation Of Industrial Wasupporting
confidence: 78%
“…2 industrial wastewater was also found to be decolorized after treatment. Similar microbial treatment of tannery wastewater for the simultaneous removal of chromate and phenolics has been reported by Srivastava et al (2007) using consortia of microbes, whereas individual removal of either phenol or Cr (VI) from tannery wastewater has been demonstrated by Paisio et al (2012) using Rhodococcus strain and Panda and Sarkar (2012) using Enterobacter aerogenes T2, respectively. …”
Section: Simultaneous Remediation Of Phenol and Cr (Vi) From Industrisupporting
confidence: 55%